Program Pembiasaan Siswa Sekolah Dasar Muhammadiyah XI Mangkuyudan Surakarta Dalam Membangun Karakter Religius - Sri Wulandari, Anisa; , Nur Amalia S. S. M.Teach (2017)
This study aims to describe the implementation of the conditioning program Mangkuyudan XI students of SD Muhammadiyah Surakarta. The research is a qualitative research with phenomenological research design. The study was conducted in SD Muahammadiyah XI Mangkuyudan Surakarta. Informant in this research is the principal, classroom teachers, and students. Data collection techniques used is a structured interview, observation and documentation. This study uses the validity of test data by triangulation. Data analysis techniques with the reduction, the display data and conclusions. The results of this study indicate that: 1) Perception Teachers to the importance of building a religious character early on as the one that underlies the holding of programs habituation form of routine activities carried out by students and teachers within their predetermined schedule, habituation spontaneous activity in the form of customs spontaneously carried out in the act, and habituation activities of an exemplary form of behavior discipline and obeying school regulation. 2) Challenges that arise in habituation activity comes from the students, playmates, family and teachers who did not master the science tadjwid, 3) To overcome the challenges that arise in the conditioning activity is to communicate directly with the mayor murit, always maintain communication with students, and for teachers who did not master the science of learning tadjwid together when the weekly meetings.